Development of Virtual Journal Club for Nurses in Improving Evidence-based Practice - Permana, Andi Fajrin (Faculty of Nursing, Universitas Hasanuddin, 2024)
Undoubtedly, Evidence-based Practice (EBP) contributes to enhanced patient outcomes, with nurses being the largest healthcare provider group. Especially in cases of poor patient prognosis, treatment decisions are often influenced by colleagues' successful approaches. Journal clubs prove effective in various learning outcomes, including enhancing knowledge, critical appraisal skills, perceived reading habits, and reading behavior. Virtual Journal Clubs (vJCs) have greater potential to address time constraints, low participant attendance, and other minor obstacles compared to traditional face-to-face journal clubs. Nurses' impact on promoting evidence-based practice is consistent across aspects such as improved knowledge, critical appraisal skills, research utilization skills, interest in conducting research, and nursing skills.